Think-Pair-Share dalam Pembelajaran Pendidikan Agama Kristen: Penelitian Tindakan Diagnostik - Danawi Danawi (Journal of Edukasi Borneo, 2022)
The purpose of this study was to explore the application of TPS in learning Christian Religious Education (PAK) at the high school level. The diagnostic action research was employed with 12 students participating. Collecting data used participatory observation and formative tests. Data from observations were analyzed qualitatively using thematic, while, formative test were analyzed statistically. The findings of this study indicated that the students responded positively to the application of TPS, and considered this technique useful, as well as the creation of cooperation and mutual respect for ideas expressed through answering questions during the discussion. In addition, although at the beginning of the cycle they still did not achieved the expected results, the student learning outcomes increased in the second cycle after the TPS was modified, namely 10 students out of 12 students were declared successful in obtaining scores according to the KKM. Thus, TPS can be said to be effectively applied in PAK learning at the high school level.   ABSTRAK Tujuan penelitian ini adalah untuk mengeksplorasi penerapan TPS dalam pembelajaran Pendidikan Agama Kristen (PAK) di tingkat SMA. Penelitian Tindakan diagnostik diterapkan dengan jumlah partisipan 12 siswa. Pengumpulan data menggunakan observasi partisipatif dan tes fomatif. Data dari hasil pengamatan dianalisis secara kualitatif menggunakan tematik dan data hasil tes formatif analisis secara statistik deskripif. Temuan penelitian ini menunjukkan bahwa siswa merespon penerapan TPS secara positif, dan menganpgap teknik ini berguna, serta terciptanya kerja sama dan saling menghargai ide yang diungkapkan melalui jawaban pertanyaan-pertanyaan saat diskusi berlangsung. Selain itu, walaupun pada awal siklus masih belum memperoleh hasil yang diahrapkan, hasil belajar siswa meningkat pada siklus kedua setelah TPS dimodifikasi, yaitu ada 10 siswa dari 12 siswa dinyatakan berhasil memperoleh skor sesuai dengan KKM. Dengan demikan, TPS dapat dikatakan efektif diterapkan dalam pembelajaran PAK di tingkat SMA. KATA KUNCI: PAK, TPS, penelitian tindakan diagnostik.